2020
DOI: 10.1016/j.cub.2020.09.036
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Cell Polarity Coupled to Growth Axis Formation in Tobacco BY-2 Cells

Abstract: Summary Several plant proteins are preferentially localized to one end of a cell, allowing a polarity to be assigned to the cell. These cell polarity proteins often exhibit coordinated patterns between neighboring cells, termed tissue cell polarity. Tissue cell polarity is widespread in plants and can influence how cells grow, divide, and differentiate [ 1 , 2 , 3 , 4 , 5 ]. However, it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 38 publications
(73 reference statements)
2
12
0
Order By: Relevance
“…Using the polarity marker BREAKING OF ASYMMETRY IN THE STOMATAL LINEAGE (BASL) in BY-2 protoplasts, it was recently shown that these isolated, spherical cells have an intrinsic polarity. 23 This fact additionally requires a polarization of the secretion machinery for delivering membrane material and proteins. To test the effect of polarized SYFO1 secretion in protoplasts, we Report generated a transgenic M. truncatula root organ culture (ROC) constitutively expressing SYFO1-GFP.…”
Section: Ligand-dependent Morphological Change Mediated By Syfo1mentioning
confidence: 99%
“…Using the polarity marker BREAKING OF ASYMMETRY IN THE STOMATAL LINEAGE (BASL) in BY-2 protoplasts, it was recently shown that these isolated, spherical cells have an intrinsic polarity. 23 This fact additionally requires a polarization of the secretion machinery for delivering membrane material and proteins. To test the effect of polarized SYFO1 secretion in protoplasts, we Report generated a transgenic M. truncatula root organ culture (ROC) constitutively expressing SYFO1-GFP.…”
Section: Ligand-dependent Morphological Change Mediated By Syfo1mentioning
confidence: 99%
“…However, ectopically expressed BASL or the binding partner BRXL shows alignment with global tissue polarity (Bringmann & Bergmann, 2017; Mansfield et al ., 2018) and with tissue scale mechanical stress (Bringmann & Bergmann, 2017). BASL polarity can also form spontaneously in tobacco BY2 cells and aligns with the axis of growth (Chan et al ., 2020). These results suggest that asymmetrical divisions could be sensitive to mechanical stress, however further work is needed to determine the mechanism and distinguish between the competing theories.…”
Section: Exceptions To the Default Rulesmentioning
confidence: 99%
“…Previous efforts to reconstruct the evolutionary history of BASL have been hampered by low overall sequence conservation beyond close relatives of Arabidopsis (Chan et al, 2020;Vatén and Bergmann, 2012), although select protein domains could be found in more distantly related species (Zhang et al, 2016a). Using a reciprocal best hit heuristic, we found a rapid drop-off in sequence similarity of candidate BASL orthologues outside the Brassicaceae, with a plateau of around 60% amino acid similarity (30% identity) for eudicots followed by a sharp drop to ~30% similarity (10% identity) for non-eudicot candidates (Figure S1A).…”
Section: Basl Is a Rapidly Evolving Eudicot-specific Genementioning
confidence: 99%
“…In fact, BSLL gene expression is enriched in the stomatal precursor zone at the base of rice and maize leaves (Wang et al, 2014). Therefore, to characterize BASL and BSLL homologues, we began by assaying the feature that best defines BASL-its polarized subcellular localization, which can be replicated in non-native contexts (Chan et al, 2020;Dong et al, 2009;Zhang et al, 2015). We expressed BASL and/or BSLL coding sequences from Arabidopsis thaliana, Solanum lycopersicum, Aquilegia coerulea and the monocot outgroup Brachypodium distachyon in developing Nicotiana benthamiana leaves (Figure S2A-B).…”
Section: Basl Is a Rapidly Evolving Eudicot-specific Genementioning
confidence: 99%
See 1 more Smart Citation